PENINGKATAN PEMAHAMAN TENTANG WAWASAN NUSANTARA (GEOPOLITIK) BAGI GENERASI MUDA DI WILAYAH PERBATASAN SEBAGAI BAGIAN DARI BELA NEGARA - Nurvianti, Dewi; Fathurrahman, Fathurrahman; Nurzamzam, Nurzamzam; Oktaviana, Arvita (Fakultas Hukum Universitas Semarang, 2023)
This Community Service appointed the title is Increasing Young Generation's Understanding of Archipelagic Insight Concept (Geopolitics) as Part of Defending the Country. The project used counseling method, it held at Senior High School namely SMAN 2 Tarakan as well as this project s partner. The program was implemented, bearing in mind that defending the country is obligation of every citizen. In a broader sense, it includes having lawful outlook towards nation and state. The conclusion after the counseling is younger generation especially students at high school in Border Region, must have a comprehensive understanding of defending the country, including understanding condition of country or must have proper perspective regarding the existence of younger generation in realizing aspirations of nation. Aftermost, the suggestion from organizer of the community service is required for continuos counseling or workshop with the output of understanding the Archipelago insight in every school involved all stakeholders.